FORMULATION AGAR AND SUCROSE SUGAR OF GREEN GRASS JELLY CANDY (Cyclea barbata Miers) - Walufi, Cici Ayu; Maherawati, Maherawati; Hartanti, Lucky (Jurnal Sains Pertanian Equator, 2020)
Jelly candy is a popular soft candy based on agar, pectin, and gum ingredient. Green grass jelly candies are one of diversify food processed. The aims of this study to obtain the best formulation of agar and sucrose in the jelly candies based on chemical and sensory properties. This study used a Randomized Block Design (RBD) by single factor that was the comparison of agar and sucrose with 5 levels consisting (2%: 41%, 2,5%: 40,5%, 3%:40%, 3,5%: 39, 5%, 4%:39%). Data was analyzed statistically by using the ANOVA test, continued by HSD test. Organoleptic data was analyzed by Kruskall Walis test. The best jelly candy produced by a formulation of 3% agar: 40% sucrose. The chemical characteristics produced were 11.99% water content, ash content 0.20%, total dissolved solids 25.33 ËšBrix, hardness level 0.09 Kgf, elasticity level 3.06 Kgf. The sensory characteristics produced were 2.97 (not green), 2.83 (no aroma), 3.63 (sweet), 3.20 (chewy), overall 3.60 (like). Keyword :grass jelly, candy, agar, sucrose